The use of infliximab in South-east Asian children with severe Crohn's disease - Lee, W.S. (2004)
Childhood Crohn's disease (CD) has a chronic relapsing course with a high morbidity which includes delayed puberty, impaired growth, and perianal disease1. It is most prevalent in North America, North-west Europe, and in the United Kingdom, and is rare in Asia1. Many children with CD eventually need corticosteroid to control symptoms1. Tumor necrosis factor Î± (TNFÎ±) is a proinflammatory cytokine which is important in the pathogenesis of CD2. Infliximab (Remicade, Schering-Plough, Kenilworth, New Jersey, USA), a chimeric anti-TNFÎ± monoclonal antibody, induces remission in patients with moderately to severely active CD and can reduce corticosteroid requirements3. We share our experience in the use of infliximab in three South-east Asian children with severe CD.